Lichen sclerosus of the oral mucosa: a hidden phenomenon - Paganelli, A.; Mandel, V. D.; Contu, L.; Motolese, A. (Frontiers in Oral Health, 2024)
Oral lichen sclerosus (OLS) represents a diagnostic challenge even for expert dermatologists due to its rarity and subtle clinical manifestations. Only few cases have been reported in literature to date. OLS typically presents with whitish macules in the oral cavity. Histopathological examination remains crucial for definitive diagnosis, with characteristic features including epithelial atrophy, subepithelial hyalinization, loss of elastic fibers, and lymphocytic infiltration. Management strategies vary depending on lesion size and symptomatic presentation, with topical or intralesional corticosteroids being the most commonly used treatment modalities. Long-term monitoring is recommended due to the potential for malignant transformation, although no cases have been reported to date. Greater awareness and understanding of OLS are essential for accurate diagnosis and effective management. Based on these findings, we recommend performing an accurate evaluation of the oral mucosa, especially when dealing with patients affected by genital or extragenital lichen sclerosus (LS). Moreover, we emphasize the importance of multidisciplinary collaboration between dermatologists and other specialists of oral disorders, such as dentists. This short review briefly summarizes available data on OLS, highlighting its diverse clinical presentations and diagnostic challenges. Despite its infrequent occurrence, OLS should be considered in the differential diagnosis of white macules in the oral cavity.